2016
DOI: 10.1371/journal.pone.0151893
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication Causes Perturbation of the Human Gut Microbiome in Young Adults

Abstract: BackgroundAccumulating evidence shows that Helicobacter pylori protects against some metabolic and immunological diseases in which the development of these diseases coincide with temporal or permanent dysbiosis. The aim of this study was to assess the effect of H. pylori eradication on the human gut microbiome.MethodsAs part of the currently on-going ESSAY (Eradication Study in Stable Adults/Youths) study, we collected stool samples from 17 H. pylori-positive young adult (18–30 years-old) volunteers. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
94
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 95 publications
10
94
0
1
Order By: Relevance
“…The up-regulation of Lipid A 12 and 18 months post- H. pylori eradication could probably be associated with the perturbation of microbiota in the gut following H. pylori eradication. In our previous fecal metagenomics study, we found a transient loss of H. pylori instantaneously following H. pylori eradication but reappeared at 12–18 months (Yap et al, 2016). Due to the overlapping time points, it is likely that H. pylori employs the advantage of ecological niche to replicate intracellularly and survive the anti-bacterial treatment (Yap et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The up-regulation of Lipid A 12 and 18 months post- H. pylori eradication could probably be associated with the perturbation of microbiota in the gut following H. pylori eradication. In our previous fecal metagenomics study, we found a transient loss of H. pylori instantaneously following H. pylori eradication but reappeared at 12–18 months (Yap et al, 2016). Due to the overlapping time points, it is likely that H. pylori employs the advantage of ecological niche to replicate intracellularly and survive the anti-bacterial treatment (Yap et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Lipid A, one of the three structural components of the lipopolysaccharide (LPS) causes the pathophysiological effects associated with Gram-negative bacteria infections (Lodowska et al, 2007). Gram-negative bacteria such as Bacteroidetes and Proteobacteria (including H. pylori ) are dominant microorganisms in the gut (Ley et al, 2005; Yap et al, 2016). The up-regulation of Lipid A 12 and 18 months post- H. pylori eradication could probably be associated with the perturbation of microbiota in the gut following H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly in this context, the microbiota in the upper gastrointestinal tract differ between H. pylori positive and negative individuals, possibly due to the observation that H. pylori infection increases gastric pH [9]. Another recent study reported that the microbiota also changed after eradication of H. pylori [10]. As the gastrointestinal microbiota is believed to substantially contribute to Crohn's disease development, a change in the In an ecological study, Helicobacter pylori and Crohn's disease are inversely correlated…”
mentioning
confidence: 99%